Opportunities of Genomics for the Use of Semen Cryo-Conserved in Gene Banks - Oldenbroek, J. Kor; Windig, Jack J. (Frontiers in Genetics, 2022)
Shortly after the introduction of cryo-conserved semen in the main farm animal species, gene banks were founded. Safeguarding farm animal genetic diversity for future use was and is the main objective. Sampling of sires was based on their pedigree and phenotypic information. Nowadays, DNA information of cryo-conserved sires and from animals in the living populations becomes available. The combination of their DNA information can be used to realize three opportunities: 1) to make the gene bank a more complete archive of genetic diversity, 2) to determine the history of the genetic diversity from the living populations and 3) to improve the performance and the genetic diversity of living populations. These three opportunities of the use of gene bank sires in the genomic era are outlined in this paper, and relevant recent literature is summarized to illustrate the great value of a gene bank as an archive of genetic diversity.